2012
DOI: 10.1007/bf03404210
|View full text |Cite
|
Sign up to set email alerts
|

Household Income, Food Insecurity and Nutrition in Canadian Youth

Abstract: here are important health disparities by income in Canada and the US. 1,2 Disadvantaged children are at greater risk of infant mortality, incidence of death from infectious diseases and accidental deaths. 3 Older youth in disadvantaged settings may be more exposed to smoking, poor diet and sedentary behaviour, contributing to an increased risk of chronic disease in adulthood. 4,5 Moreover, the contribution of these exposures to increased morbidity and mortality appears to be additive, 6 and clustering of risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 30 publications
5
38
2
1
Order By: Relevance
“…Earlier studies also suggest that food insecurity is a marker of nutrition inequity in Canada (10,18). Studies conducted in the United States have similarly suggested compromises in diet associated with food insecurity (7,9,15,16), although our study revealed less difference by food security status in the United States than has been reported previously.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Earlier studies also suggest that food insecurity is a marker of nutrition inequity in Canada (10,18). Studies conducted in the United States have similarly suggested compromises in diet associated with food insecurity (7,9,15,16), although our study revealed less difference by food security status in the United States than has been reported previously.…”
Section: Discussioncontrasting
confidence: 55%
“…Analyses of data from Canadian Community Health Survey cycle 2.2 were supported by funds from a Programmatic Grant in Health and Health Equity, Canadian Institutes of Health Research (FRN 115208), held by VT. ability to access adequate food (2,3), is a marker of nutritional vulnerability. Studies in Canada, the United States, and New Zealand have shown compromised food and nutrient intakes among those struggling with food insecurity (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Furthermore, food insecurity is associated with risk and management of diet-sensitive chronic diseases, including cardiovascular disease and diabetes, in both Canada and the United States (20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, food insecurity and socio-biological stress, as observed in the studied area, can slow down healthy growth, which can affect future health; for example, low stature in adult women resulting from malnutrition during childhood and adolescence is related to increased gestational risks (Ramakrishnan, 2004). Mark et al (2012) observed similar results in a nationally representative study in Canada where low-income adolescents presented lower intakes of calcium and vitamin D and lower height percentiles than those from higher-income households, even though there were no differences in the height percentiles according to the level of food insecurity. However, some studies have observed a higher prevalence of overweight in adolescents from families living in food insecurity compared with those that did not report food insecurity (Alaimo et al, 2001;Casey et al, 2001Casey et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies identified were from North America (91 from the USA and 10 from Canada), 21,23,27,42,43,45,46,68,75,76 five were from the UK, 19,[30][31][32]59 one was from Ireland, 106 one was from Australia 54 and one was from New Zealand. 122 Of the 109 studies included in the review, 100 were quantitative studies, 9,12,[18][19][20][21][22][23][24][26][27][28][29]33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][56]…”
Section: Chapter 3 Resultsmentioning
confidence: 99%
“…122 Of the 109 studies included in the review, 100 were quantitative studies, 9,12,[18][19][20][21][22][23][24][26][27][28][29]33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][56][57][58]60,61,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][7...…”
Section: Chapter 3 Resultsmentioning
confidence: 99%